Demystifying App Performance Optimization: From Cold Starts to Seamless Transitions - Arth Patel, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the critical aspects of mobile application performance optimization, focusing on the relationship between technical efficiency and user satisfaction. The article examines various performance metrics, including latency, frame rates, memory usage, and cold start times, while analyzing their impact on user engagement and business outcomes. Through detailed explanation of common performance challenges and optimization strategies, the article provides insights into effective development practices, testing methodologies, and resource management approaches. The article combines empirical data from multiple studies to demonstrate the significance of systematic performance optimization in mobile application development, offering practical solutions for developers and stakeholders to enhance application performance across different operational scenarios.
Keywords: Android performance optimization; app responsiveness metrics; memory management strategies; mobile application efficiency; user experience optimization